Development of smooth particle hydrodynamics for the modelling of stresses around jack-in pile - Cyril, Perpetua Aaniya (2020)
Jack-in pile installation generates large deformations in the surrounding soil. These deformations cause significant changes to the soil stress levels. Such variations in stresses greatly influence the pile bearing capacity. Therefore, prediction of stresses in soil during the installation phase is crucial. However, over the past, limited knowledge has been gained on soil stress field during jack-in pile installation. The experimental techniques available for obtaining soil stress measurements involve a great level of complexity. Accurate simulation of the stress field necessitates pile to be modelled as an elastic or elastic-perfectly plastic material from the soil surface considering soil-pile interaction. However, most of the numerical models in the literature based on mesh-based or mesh-free methods have adopted various simplified assumptions in modelling the phenomenon. The models have provided limited knowledge regarding the progress of soil stress distribution with pile penetration. Furthermore, Smooth Particle Hydrodynamics (SPH), a renowned and a promising numerical approach for large deformation applications is yet unexplored in this field of research. Therefore, with mounting demand in SPH, current dissertation presents the development of SPH model for simulating soil stress field around jack-in pile. Unlike the numerical models in the literature, the SPH model is introduced with minimised simplified assumptions and increased capabilities for delivering precise estimation and comprehensive understanding of the soil stress field.